Persepsi Mahasiswa Institut Bisnis dan Informatika Kosgoro 1957 Terhadap Kualitas Pelayanan di Program Studi Administrasi Bisnis - Sylvia Kartika Dhamayanti (Journal on Education, 2023)
This study aims to examine the perceptions of Kosgoro 1957 Institute of Business and Informatics students' perceptions of the service quality of the Business Administration Study Program. The sampling method used is a simple random sampling method organized by educational staff. The research informants consisted of 100 students who had received and are currently receiving academic administration services. The perception assessment method uses the scoring method and continues with the perception category based on the score that has been generated. Student perceptions of service expectations are not matched by the performance of educational staff, they argue that the quality of services provided is quite optimal. These findings indicate that perceived service quality is less than student expectations on several service quality dimensions. Namely, tangible, reliability, responsiveness, assurance and empathy. Therefore, to improve the quality of service to students, what needs to be improved is; (1) standard operating procedures (SOP); (2) speed and timeliness of service; (3) discipline of educational staff.